Development and Validation of Force Test to Assess Physics Education Students' Representational Competence - Judyanto Sirait*; Firdaus Firdaus; Muhammad Musa Syarif Hidayatullah; Ray Cinthya Habellia (Jurnal Pendidikan Sains Indonesia, 2023)
Force is one the physics cocncepts which is challenging for students. Several tests have been developed to measure students’ understanding about force. However, the instruments for assessing students’ competence to represent force concepts in various formats are limited. This study aims to develop and validate a multiple-choice test to assess students’ representational competence of force. Research and Development research is implemented in producing the test. The test includes three representations: graphs, equations, and words or descriptions which covers two contexts: on horizontal surface and on inclined plane. Moreover, this test involves three different situations namely an object is at rest, moving with constant velocity, and moving with constant acceleration. Each representation consists of 10 items and the total of items is 30. This test is administered to 51 undergraduate physics education students. The results show that the range of item difficulty index is 0.07-0.64 and discrimantory power is from 0.14 to 1.00. The reliability index for representational competence test of force to be 0.80 which is sufficiently high measurement. These results suggest that couple items of the test need to be revised before administering to the large sample